Obesity management: Attitudes and practice of Italian endocrinologists - Chianelli, Marco; Busetto, Luca; Attanasio, Roberto; Disoteo, Olga Eugenia; Borretta, Giorgio; Persichetti, Agnese; Samperi, Irene; Scoppola, Alessandro; Paoletta, Agostino; Grimaldi, Franco; Papini, Enrico; Nicolucci, Antonio (Frontiers in Endocrinology, 2023)
Introduction Obesity is a global pandemic and is cause of serious concern in all regions of the world. It is important to raise the attention of health care professionals in order to provide early treatment of patients with obesity. Obesity management, however, varies greatly amongst endocrinologists with respect to attitudes to diagnosis and treatment. Aim of this study was to identify practices and needs of Italian endocrinologists with respect to people with obesity. Methods In this study, all members of the Italian Association of Clinical Endocrinologists (AME) were invited to participate in a web-based survey concerning the management of obesity. Results The response rate was 24.1% (542/2248). Nutritional and obesity problems were reported as major areas of interest by 29.4% of the participants. A large proportion of patients seeking an endocrine consultation for other reasons are affected by obesity, but one in five respondents addressed the issue in 25% or less of the cases, while one in three always dealt with the problem. Obesity was managed personally/within a dedicated team by 42.6% of participants, while the remainders referred the patient to a dietician/nutritionist or a 2nd level center for obesity therapy. Metformin was used in a median of 30% of the patients (Interquartile range: 10-50) and liraglutide in 10% of the cases (IQR 0-30), while orlistat (median 0%; IQR 0-10) and naltrexone/bupropion (median 0%; IQR 0-5) were seldom prescribed. Cost of therapy was considered as the major limitation to the use of anti-obesity drugs, affecting adherence to long-term treatment. According to 41.9% of respondents, psychological support should be offered to all patients with obesity. Finally, 56% of participants believe that the availability of new drugs will increase the number of patients candidate to drug therapy. Discussion In conclusion, it is of primary importance to raise the awareness of endocrinologists towards the problem of obesity and increase their confidence in managing this pathological condition.